Phenotypic Identification of Streptococcus mutans and Attendant Bacteria From Dentin Caries and Necrotic Pulp, and Its Correlation with Caries Activities Tests - Enas Yaseen Shehab; Basima A. Abdullah; Anmar A. AlTaie (Medical Journal of Babylon)
Background: Dental caries is a worldwide disease, which can affect all ages and sexes. The dominant bacteria and the first colonizer in dental plaque are Streptococcus mutans due to its adhesion to the hard surface, metabolizing of sugar, and forming tooth cavity if not treated will reach the root pulp, producing necrotic pulp. Objectives: The current study was designed to detect S. mutans and attendant bacteria in the oral cavity of patients with two types of caries (dentin caries and necrotic pulp), and its relation with MDFT score and Alban test. Materials and Methods: Two samples were collected from every 150 patients including one from dentin caries and the other from necrotic pulp, who have attended the Dental Teaching Hospital at the University of Mosul, in Mosul, Iraq with ages ranging between 6 and 76 years, and both sexes, from the beginning of March 2022 to the end of October 2022. Results: VITEK 2 compact system used to identify of S. mutans at a high number of 39 (32.5%) in dentin caries while Enterococcus faecalis gave a high number of 43 (35.8%) in necrotic pulp in addition to other different bacterial species were identified as Streptococcus sanguinis, Streptococcus gordonii, Streptococcus anginosus, Lactococcus acidophilus, Staphylococcus aureus, Actinomycus spp., Staphylococcus hominis, Enterococcus faecium, Lactococcus lactis, Lactococcus garvieae, Lactococcus raffinolactis, Kocuria rosea, Pediococcus acidilactici, Pediococcus pentosaceus, and the fungal Candida albicans. The sex had no significant correlation with other factors, while age had a significant effect at P < 0.05 level and pH of saliva had a significant effect at P < 0.01 with DMFT and lactobacillus count. The DMFT had a significant effect at P < 0.01 level with pH of saliva and count of S. mutans and Lactobacillus count at P < 0.05. Conclusions: The current study concluded that the cariogenic bacteria S. mutans was the most prevalent in dentin caries (carious lesion), and E. faecalis was the most prevalent in necrotic pulp by using VITEK 2 compact system, and the caries activities tests show pH of saliva had a significant effect with DMFT and lactobacilli colonies count and Streptococci colonies count.